PENINGKATAN KETERAMPILAN PASSING BAWAH BOLA VOLI MELALUI STRATEGI PEMBELAJARAN SESAMA TEMAN PADA SISWA KELAS IV SD NEGERI 001 EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Ernailis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study includes: (1) the majority of students are reluctant to play volleyball because they find it difficult; (2) many students still do not perform the basic volleyball motions correctly; and (3) most students have not yet mastered the underhand pass, making it difficult to direct the ball to their peers. This study aims to determine the learning outcomes of underhand passing using the peer teaching learning strategy for fourth-grade students at SD Negeri 001 Empat Balai, Kecamatan Kuok, Kampar. The research was conducted with fourth-grade students of SD Negeri 001 Empat Balai, Kecamatan Kuok, Kampar, over a period of four months, from January 2015 to April 2015. This study employed a classroom action research design. The research instruments consisted of observation sheets for both teacher and student activities, as well as performance assessment tools. Based on the results and discussion, the basic motor skills of underhand passing for fourth-grade students at SD Negeri 001 Empat Balai, Kecamatan Kuok, Kabupaten Kampar could be improved through peer teaching strategies. This conclusion is supported by the following findings: (1) the initial test of students’ abilities before applying the peer teaching strategy showed an average score of 64.7, categorized as fairly competent; (2) in the first cycle, the average student ability increased to 71.1, categorized as competent; and (3) in the second cycle, the average student ability reached 77.1, still in the competent category, with 80% completeness. This indicates that the classical completeness has been achieved, as the research is considered successful if at least 80% of students score a minimum of 70.